Failure case studies : steel structures - Nastar, Navid; Liu, Rui (Structural engineer) (Failure case studies, 2019)
"This book gives examples of failed civil engineering projects and the lessons learned from the failures. The case studies were gathered by ASCE's Forensic Engineering Division"--